Humoral Immune Response to Clostridioides difficile Toxins A and B in Hospitalized Immunocompromised Patients With C difficile Infection. (1st June 2021) - Alonso, Carolyn D; Papamichael, Konstantinos; Sprague, Rebecca; Barrett, Caitlin; Gonzales-Luna, Anne J; Daugherty, Kaitlyn; Garey, Kevin W; Villafuerte-Gálvez, Javier; Xu, Hua; Lin, Qianyun; Wang, Lamei; Chen, Xinhua; et al.
Abstract: Background: The humoral immune response to Clostridioides difficile toxins in C difficile infection (CDI) is incompletely characterized in immunocompromised hosts (ICHs). Methods: We conducted a prospective study of hospitalized adults with CDI, with and without immunosuppression (hematologic malignancy, active solid tumor, solid organ or stem cell transplant, inflammatory bowel disease, autoimmune disease, congenital or acquired immunodeficiency, asplenia, chronic receipt of high-dose steroids, or receipt of immunosuppressing medications within 12 months). Serum and stool antibody concentrations of immunoglobulin (Ig)M, IgG, and IgA to C difficile toxins A and B at treatment days 0, 3, and 10–14 were compared. Results: Ninety-eight subjects (47 ICH; 51 non-ICH) were enrolled. Baseline serum antitoxin A and B antibody levels were similar. At day 3, ICHs demonstrated lower serum levels of antitoxin A IgG, antitoxin A IgA, and antitoxin B IgA (all P < .05). At day 10–14, lower antitoxin A IgG concentrations were observed in ICHs (ICH, 21 enzyme-linked immunosorbent assay [ELISA] units; interquartile range [IQR], 16.4–44.6) compared with non-ICH subjects (49.0 ELISA units; IQR, 21.5–103; P = .045). In stool, we observed lower concentrations of antitoxin B IgA antibodies at baseline and at day 3 for ICH subjects, with a notable difference in concentrations of antitoxin B IgA at day 3 (ICH, 6.7 ELISA units [IQR, 1.9–13.9] compared with non-ICH, 18.1 ELISA units [IQR, 4.9–31.7]; P = .003). Conclusions: The ICHs with CDI demonstrated lower levels of C difficile antitoxin antibodies in serum and stool during early CDI therapy compared with non-ICHs. These data provide insight into the humoral response to CDI in ICHs. Abstract : Immunocompromised patients with CDI demonstrated lower levels of Clostridioides difficile toxin-specific antibodies in the serum and stool at treatment day 3 compared with non-immunocompromised subjects. These data provide insight into the natural history of CDI humoral response in immunocompromised subjects.